HUBUNGAN ANTARA KARAKTERISTIK IBU DENGAN KELENGKAPAN IMUNISASI DASAR DI PUSKESMAS WONOKUSUMO KOTA SURABAYA - Larassita Rakhmanindra; Nunik Puspitasari (The Indonesian Journal of Public Health, 2019)
Immunization is one of the main activities implemented by the Ministry of Health in order to decrease the number of child pain and mortality caused by diseases that can be prevented by immunization (PD3I). This research aims to analyze the correlation between the mother characteristics and complete basic immunization on infants at Wonokusumo Community Health Service, Semampir District, Surabaya. The research is analytical study by employing cross-sectional design. The research samples were 86 mothers taken by using simple random sampling techniques. The data collection was carried out by conducting interview based on the existing questionnaire to mothers with 1-2 years children in Wonokusumo area. The analyzed variables were mother’s age, knowledge, employment status, income level, antinatal maternal status, and motivation. The data analysis was carried out by Chi-Square.The results show that there is a correlation of the mothers’ formal education (p=0.005), mothers’ knowledge about immunization (p=0.000), income level (p=0.018), antenatal maternal status (p=0.000), and the mother’s motivation (p=0.000) and complete basic immunization. Meanwhile, the mothers’ age (p=0.849) and mothers’ employment status (p=0.059) have no correlation with the complete basic immunization. In conclusion, the mother’s formal education, knowledge about immunization, income level, antenatal maternal status, and motivation are crucial matters in conducting complete basic immunization.